Synthesis and Characterization of Novel Mesoporous CuO and Its Application to CO2 Capture - Mei Peng, Mei; Hemalatha, Pushparaj; Ganesh, Mani; Vinodh, Rajangam; Tae Jang, Hyun (Asian Journal of Chemistry, 2013)
A new mesoporous CuO nanoparticles has been synthesized successfully by using mesoporous carbon as template and cupric nitrate trihydrate (Cu(NO3)2·3H2O) as copper source. The synthesized meso porous CuO was characterized with XRD, TGA, SEM and BET. The result revealed that the synthesized porous CuO has high mesoporous surface area and crystal structure with uniform sized spherical crystal particles. The specific surface area (SBET) of synthesized CuO was found to be 153.46 m2 g-1 with a total pore volume (Vp) of 0.1516 cm3 g-1 and average pore size of 3.9 nm, which was much higher than that of commercial CuO (SBET, 7.6 m2 g-1; Vp, 0.01 cm3 g-1). The CO2 studies also revealed that the synthesized CuO nanoparticles have maximum CO2 adsorption of about 75 mg/g (7.5 wt %) at room temperature and pressure.